Phytochemical and Toxicity Analysis of Sonneratia alba Mangrove Leaf Extract using the Brine Shrimp Lethality Test (BSLT) Method - Arta, Ni Kadek Dewi Asri Tiara; Indraningrat, Anak Agung Gede; Wijaya, Made Dharmesti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Mangroves are plants that contain various secondary metabolites with various potential pharmacological activities, one of which is cytotoxic activity. However, researchers have not extensively explored the evidence of secondary metabolite compounds and their toxicity effects in mangrove plants. This research aims to determine the content of secondary metabolite compounds and the toxicity of the leaf extract of the Sonneratia alba mangrove plant in the Ngurah Rai Grand Forest Park (TAHURA), Bali. In this experimental research, compound extraction was carried out using a maceration technique for 2x24 hours using two types of solvents, namely methanol and n-hexane. Phytochemical tests were carried out using qualitative methods and gas chromatography-mass spectrometry (GC-MS), while the toxicity test used was the brine shrimp lethality test (BSLT) method. Potassium dichromate and sea water without extract were used as positive and negative controls, respectively. The LC50 value was calculated using probit analysis in Microsoft Excel. Phytochemical test results showed that the methanol extract contains phenol, saponin, tannin, and steroid compounds. Meanwhile, n-hexane extract only contains steroid compounds. GC-MS analysis showed that the compounds with the largest area percentages in the methanol and n-hexane extracts were 1,2,3-benzenetriol (3.94%) and n-hexadecenoic acid (2.41%), respectively. Based on the LC50 value, the methanol extract of S. alba mangrove leaves was moderately toxic (178.17 ppm), while the n-hexane extract was weakly toxic (567.23 ppm). The results of this study provide information that the type of chemical solvent has a major influence on the level of toxicity of S. alba leaf extract, with polar methanol solvent providing the highest toxicity effect compared to nonpolar n-hexane solvent.